ANALYSIS OF SHORELINE CHANGES ON KRUI BAY, WEST COAST OF LAMPUNG PROVINCE - S. Panalaran; T. A. Tarigan; N. Simarmata (Journal of Science and Applicative Technology, 2019)
Shoreline change is a natural process caused by the transported sediment generated by nearshore current to preserve the mass rates. Shoreline change can be a shoreline loss called abrasion as well as shoreline expansion due to sedimentation called accretion. Abrasion and accretion phenomenon can be regarded as a threat if they cause damage or potentially disrupts human activity. Identification of land use as well as geographical and physical condition of a region can be approached by satellite image analysis. This research uses Landsat Satellite imagery to observe shoreline changes based on the position of shoreline recorded through satellite images of 2004, 2010, and 2016. The image of one period overlapped with other period images is used to calculate the increment or decrease of shoreline occurring at a particular location. The results of this study will show the trend of increasing or decreasing the shoreline based on certain time and position